Лушкем яратон: кылбуръёс / Алла Кузнецова - Кузнецова Алла Алексеевна (Удмуртия, 1995)
Экземпляры: ф.5 (1996) / Инвентарный номер: 39305 / Цена: / Сис.шифр: 84(2Рос=Удм)6-5 / Авт.знак: К 89 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6-5